The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10441-010-9107-8
|View full text |Cite
|
Sign up to set email alerts
|

The Sunk-cost Effect as an Optimal Rate-maximizing Behavior

Abstract: Optimal foraging theory has been criticized for underestimating patch exploitation time. However, proper modeling of costs not only answers these criticisms, but it also explains apparently irrational behaviors like the sunk-cost effect. When a forager is sure to experience high initial costs repeatedly, the forager should devote more time to exploitation than searching in order to minimize the accumulation of said costs. Thus, increased recognition or reconnaissance costs lead to increased exploitation times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Traveling to new patches and the effort associated with capturing new prey (e.g., trial and error) are costly and may not yield an immediate energetic gain, however, greater familiarity with various food patches and improvement in efficiency of capturing prey may yield a net energy profit over an animal’s lifetime or that of its offspring [27,76,77]. A possible example of this would be the pursuit and capture of flightless waterfowl on land by polar bears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traveling to new patches and the effort associated with capturing new prey (e.g., trial and error) are costly and may not yield an immediate energetic gain, however, greater familiarity with various food patches and improvement in efficiency of capturing prey may yield a net energy profit over an animal’s lifetime or that of its offspring [27,76,77]. A possible example of this would be the pursuit and capture of flightless waterfowl on land by polar bears.…”
Section: Discussionmentioning
confidence: 99%
“…They would permit the bears to maximize calorie intake while minimizing energy expenditures associated with movement [12]. Non-energetic benefits, such as fulfilling vitamin/mineral requirements, diluting toxins, assessing new resources and learning processes, may also motivate seemingly unprofitable foraging behaviors [5,67,76,77]. …”
Section: Discussionmentioning
confidence: 99%
“…Most chases of terrestrial prey we observed involved a short burst of running of less than a minute although some lasted longer (e.g., Iles et al, 2013). Polar bears engaging in longer chases could be in the process of learning (Pavlic and Passino, 2011;Iles et al, 2013) or deliberately attempting to tire and separate out vulnerable prey, a technique commonly used by grizzly bears (e.g., Gunther and Renkin, 1990). This is likely an energetically more costly tactic than ambushing or stalking but may be profitable, particularly for smaller bears (Gormezano et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…Braverman and Blumenthal-Barby (2012) defined the sunk cost effect as the tendency to follow a course of action, even after it has proved to be ineffective because the resources have already been invested. Such perspective may be a justification for people who choose to pursue an investment with a conscience who will not achieve the expected results just because they have already invested some resource and do not reflect on a more effective, more viable and less harmful alternative to correct the situation (Pavlic & Passino, 2010).…”
Section: Sunk Costs Effectmentioning
confidence: 99%